Characteristics of drowning by different age groups. Issue 2 (1st June 2003) - Quan, L; Cummings, P
Abstract : Context : While it is known that the risk of unintentional drowning varies with age, the manner in which drowning episode characteristics vary by age has not been well described. Such information might be useful for prevention. Objective : To describe characteristics of drowning by age group. Design: Retrospective review of the characteristics of drowning victims and their drowning incidents obtained from death certificates, medical examiner, pre-hospital, emergency department, and hospital records. Setting: Three counties in Western Washington state. Subjects: Residents who died (n=709) of unintentional drowning within the study region during 1980 through 1995. Outcomes: Age specific counts, proportions, and rates per million person years were estimated for and compared among six age groups. R esults: Rates varied by age group: 0–4 (30.5), 5–14 (11.6), 15–19 (29.9), 20–34 (21.5), 35–64 (12.5), and 65 years or older (21.2). Among those 0–4 years, the proportions that drowned in pools, bathtubs, and open water were nearly equal. But from age 5–64 years, over 69% of deaths were in open water. Among those 65 years and older, the deaths were almost evenly divided between bathtub and open water; bathtub drowning rates were highest in this age group, 10.9. Pre-drowning activities were divided into boating, swimming, car passenger, bathing, and fell in while doing something else. Most (64/89, 76%) victims aged 0–4 years drowned while bathing or after falling in. Among those 15–19 years, most occurred while swimming (24/79, 34%) or boating (22/79, 31%). The drowning event was least often witnessed among those 0–4 years (10/36, 28%), and most often witnessed (44/58, 76%) among those 15–19 years. Medical care (pre-hospital, emergency department, or hospital) was most often involved in drownings of those 0–4 years (70/89, 79%) and least among those over 65 years (11/86, 13%). Conclusion: The characteristics of drowning episodes vary greatly by age. Different prevention strategies may be needed for different age groups.